Predictive value of tachycardia for mortality in trauma-related haemorrhagic shock: a systematic review and meta-regression. Issue 10 (19th October 2022) - Jávor, Péter; Hanák, Lilla; Hegyi, Péter; Csonka, Endre; Butt, Edina; Horváth, Tamara; Góg, István; Lukacs, Anita; Soós, Alexandra; Rumbus, Zoltán; Pákai, Eszter; Toldi, János; et al.
Abstract : Objectives: Heart rate (HR) is one of the physiological variables in the early assessment of trauma-related haemorrhagic shock, according to Advanced Trauma Life Support (ATLS). However, its efficiency as predictor of mortality is contradicted by several studies. Furthermore, the linear association between HR and the severity of shock and blood loss presented by ATLS is doubtful. This systematic review aims to update current knowledge on the role of HR in the initial haemodynamic assessment of patients who had a trauma. Design: This study is a systematic review and meta-regression that follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses recommendations. Data sources: EMBASE, MEDLINE, CENTRAL and Web of Science databases were systematically searched through on 1 September 2020. Eligibility criteria: Papers providing early HR and mortality data on bleeding patients who had a trauma were included. Patient cohorts were considered haemorrhagic if the inclusion criteria of the studies contained transfusion and/or positive focused assessment with sonography for trauma and/or postinjury haemodynamical instability and/or abdominal gunshot injury. Studies on burns, traumatic spinal or brain injuries were excluded. Papers published before January 2010 were not considered. Data extraction and synthesis: Data extraction and risk of bias were assessed by two independent investigators. The association between HR and mortality of patients who had a trauma was assessed using meta-regression analysis. As subgroup analysis, meta-regression was performed on patients who received blood products. Results: From a total of 2017 papers, 19 studies met our eligibility criteria. Our primary meta-regression did not find a significant relation (p=0.847) between HR and mortality in patients who had a trauma with haemorrhage. Our subgroup analysis included 10 studies, and it could not reveal a linear association between HR and mortality rate. Conclusions: In accordance with the literature demonstrating the multiphasic response of HR to bleeding, our study presents the lack of linear association between postinjury HR and mortality. Modifying the pattern of HR derangements in the ATLS shock classification may result in a more precise teaching tool for young clinicians.